Zinc Acetate as a Catalyst: Improved Method of Protection of Amino Group in Synthesis of Nucleobase Derivatives and its Biological Applications (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
2-(2,4-dioxo-1,2,3,4-tetrahydropyrimidin-5-yl)-1H-benzoisoquinoline-1,3(2H)-dione was synthesized by reacting 5-amino uracil with 1,8-naphthalic anhydride in the presence of zinc acetate as a catalyst and screened for the in-silico/in-vitro antimicrobial activities. All the analyzed physicochemical descriptors (viz. drug-likeness, bioactivity score, and absorption, distribution, metabolism, excretion, and toxicity (ADMET)) of the compound provide an impetus to the docking results obtained by simulating against the catalytic site of Escherichia coli peptide deformylase enzyme (PDF, PDB ID: 1G2A) and allosteric site of human immunodeficiency viruses (HIV) reverse transcriptase enzyme (PDB ID: 3MEC). Docking results revealed that the compound has interacted well with the amino acid residues Lys103, Lys101, and Pro 236 of non-invasive blood pressure (NIBP) of human immunodeficiency viruses (HIV) reverse transcriptase (RT) and Ile44, Gly89, Leu91, and Glu133 of peptide deformylase (PDF). The predicted free binding energy ΔG (-6.83 kcal/mol) showed that the compound formed a stable complex with PDF protein receptor, thus, can behave as a probable drug regimen in antibiotics. Whereas, the calculated total binding energy (-38.87 kcal/mol) alluded to the anti-HIV property of the compound as probable nucleoside reverse transcriptase inhibitor (NNRTI). In-vitro antibacterial screening, results exhibited promising inhibitory activity against Pseudomonas aeruginosa and E. coli (MIC value, 12.5 and 25 μg/mL, respectively).